2008
DOI: 10.2341/07-69
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorhexidine Application on Microtensile Bond Strength to Dentin

Abstract: ©Operative Dentistry, 2008, 33-2, 183-188 SUMMARYThis study evaluated the effect on microtensile bond strength (µTBS) of chlorhexidine application to dentin at different times during an indirect restoration luting procedure. Sixty bovine incisors had their superficial dentin subjected to 0.12% and 2% chlorhexidine solutions for 15 seconds before, during and after 37% phosphoric acid etching, resulting in six groups (n=10): 1) 0.12% chlorhexidine + etching; 2) 2% chlorhexidine + etching; 3) etching + 0.12% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
44
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 33 publications
8
44
2
4
Order By: Relevance
“…The use of CHX along with total etch adhesive resins does not impair their ability to bond to dentin. 14,16,[27][28][29][30][31] This finding is in agreement with the present study where a bisphenol A-glycidyl methylmethacrylate (Bis-GMA)/hydroxyethyl methacrylate (HEMA) three-step etch and rinse adhesive system was used along with a conventional dual resin cement.…”
Section: Discussionsupporting
confidence: 81%
“…The use of CHX along with total etch adhesive resins does not impair their ability to bond to dentin. 14,16,[27][28][29][30][31] This finding is in agreement with the present study where a bisphenol A-glycidyl methylmethacrylate (Bis-GMA)/hydroxyethyl methacrylate (HEMA) three-step etch and rinse adhesive system was used along with a conventional dual resin cement.…”
Section: Discussionsupporting
confidence: 81%
“…The results of the present study are consistent with the results of previous studies on total-etch and two-step selfetch adhesives (de Castro et al, 2003;Bocangel et al, 2000;Soares et al, 2008;Perdigao et al, 1994;Erhardt et al, 2008). They showed that chlorhexidine had no negative effects on the bond strength of adhesive systems, which might be attributed to the compatibility of chlorhexidine with the adhesive resins used.…”
Section: Discussionsupporting
confidence: 83%
“…Interaction between the positive and negative charges produces an affinity in chlorhexidine molecules for bacteria. The interaction between chlorhexidine molecules and bacteria increases the permeability of bacterial cell membranes, resulting in the penetration of destructive agents into the cytoplasm and the ultimate death of the microorganism (Soares et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On factors that may affect the chemical interaction between restorative materials and dentin, and perhaps even the sealing and bonding properties of luting agents, they include the ingredients of desensitizers, antibacterial solutions, and hydrogen peroxide. Besides, saliva and blood contamination may also create a thin film on the dentin surface that hinders adhesive penetration into the dentinal tubules 10,13,14) . In the wake of these concerns, the present study evaluated the effects of various dentin surface treatments (desensitizer, disinfectant, saliva, blood, hydrogen peroxide, no treatment [wet dentin]) on the tensile bond strengths of the adhesive-dentin interface and adhesive-ceramic (lithium disilicate glass ceramic) interface.…”
Section: Introductionmentioning
confidence: 99%